Thin films of organic molecular crystals (OMC) possessing type B lattice: spatial structure of dibenzotetraazaannulene film is related to its thickness - Snopok, B.A.; Lampeka, Ya.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Diffractometric and optical measurements showed that at considerable (>200 oK) difference between sublimation temperature and substrate one dibenzotetraazaannulene forms well oriented films structure of which depends on their thickness. This phenomena was explained by assuming that the temperature gradient inside the film can be changed during the evaporation. Therewith, both diffusion processes in clusters and the restructurization of small crystallites were suggested to be important components of OMC film formation mechanism.